Integrating Online Project-Based Learning to Improve Critical Thinking and Arabic Writing in Pesantren - Friendis Syani Amrulloh (Academia Publication, 2025)
While pesantren education has a strategic role in developing critical thinking and creative writing skills in Arabic, traditional approaches often lack relevance in the digital era. This study aims to examine the effectiveness of online project-based learning (PJBL) as an innovative approach to improve students' competencies. Using a quasi-experimental design with a non-randomized sampling method, this study involved students who participated in online PjBL learning. Data analysis was conducted through an ANOVA test to measure the improvement in critical thinking and creative writing skills. The results showed that online PjBL significantly improved critical thinking (p = 0.001) and creative writing (p = 0.000). Although effective, challenges such as limited technological infrastructure and teacher readiness remain obstacles. This study recommends that pesantren adopt technology-based learning methods to prepare students for 21st-century competencies. Further research is recommended to expand the scope of the area, increase the study duration, and involve government policy support, so that the results of applying this method can be more optimal and sustainable.